Phyllanthus chacoensis (Phyllanthaceae): new record for the Brazilian Amazon and its lectotypification - Jone Clebson Ribeiro MENDES; Ricardo de S. SECCO; Sarah Maria ATHIÊ-SOUZA; Margareth Ferreira de SALES (Acta Amazonica, 2021)
ABSTRACT The first record of Phyllanthus chacoensis for the Brazilian Amazon is presented, based on a specimen from Rondônia state. The species can be recognized by its cauliflorous inflorescence, staminate and pistillate flowers with 4 sepals, devoid of a floral disk, 4 stamens, 2-carpellary ovary, drupaceous, ellipsoidal fruits, with one seed per locule. The species was previously known only from the central-western and northeastern regions of the Caatinga and Pantanal domains in Brazil. We provide a list of synonyms, a detailed description, an updated geographic distribution map in Brazil, data on habitat and conservation status, illustrations of its reproductive characters, and detailed photographs. We also propose a lectotype for the species.